Acoustical Analysis and Drilling Process Optimization of Camellia Sinensis / Ananas Comosus / GFRP / Epoxy Composites by TOPSIS for Indoor Applications. Issue 12 (2nd December 2021) - Gokulkumar, S.; Thyla, P.R.; ArunRamnath, R.; Karthi, N.
ABSTRACT: Camellia Sinensis/Ananas Comosus/GFRP/Epoxy Polymer composites are widely accepted to be a better material for indoor sound damping. It has a series of challenges, like force cuts on the drilling of these composites. The focus is to drill on hybrid laminates by changing the cutting conditions like the speed and feed and the selection of optimum machining process parameters. Nine experimental cycles have been performed, and five various attributes were analyzed, for example, torque, tangential force, thrust force, and also the factor of delamination (Enter & Exit). This study shows a sequential parameter selection for the drilling machining process. Using Multi-attribute optimization, order preference and optimum drilling machining process parameters are selected by the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). From the TOPSIS analysis, the best suitable optimum drilling conditions for hybrid laminates are chosen as 600 rpm and 0.02 m/min for cutting speed and feed rate, respectively.